Pengembangan LKPD Berbasis Komik pada Materi Bilangan Bulat untuk Meningkatkan Pemahaman Matematis Siswa Kelas VII - Aini, Jumratul; Astuti, Reni; Abdillah, Abdillah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to produce a product in the form of a comic-based worksheet that is seen from the level of validity, practicality and effectiveness so that it can be used in the learning process. The type of research used in this research is Research and Development (R&D) with a Borg and Gall research design. This research was carried out at SMP Negeri 1 Tanah Pinoh, Melawi, West Kalimantan with research subjects of 30 class VII students. The instruments used in this research were material and media validation sheets, teacher and student response questionnaires, and mathematical understanding posttest sheets. From the research results, it was found that the comic-based worksheet that was developed was suitable for use in the learning process with the criteria